Inverse Effects of Oxytocin on Attributing Mental Activity to Others in Depressed and Healthy Subjects: A Double-Blind Placebo Controlled fMRI Study - Pincus, David; Kose, Samet; Arana, Ashley; Johnson, Kevin; Morgan, Paul; Borckardt, Jeffrey; Herbsman, Tal; Hardaway, Fran; George, Mark; Panksepp, Jaak; Nahas, Ziad (Frontiers in Psychiatry, 2010)
Background: Oxytocin is a stress-attenuating and pro-social neuropeptide. To date, no study has looked at the effects of oxytocin in modulating brain activity in depressed individuals nor attempted to correlate this activity with attribution of mental activity in others. Method: We enrolled 10 unmedicated depressed adults and 10 matched healthy controls in a crossover, double blind placebo controlled fMRI 40 i.u. intra-nasal oxytocin study (20 i.u. per nostril). Each subject performed reading the mind in the eyes task (RMET) before and after inhalation of oxytocin or placebo control for a total of 80 scans. Results: Before oxytocin administration, RMET engaged the medial and lateral prefrontal cortex, amygdala, insula and associative areas. Depressed subjects showed increased anterior ventral activation for the RMET minus gender identification contrast whereas matched controls showed increased dorsal and frontal activity. Compared to placebo, oxytocin in depressed subjects showed increased activity in the superior middle frontal gyrus and insula, while controls exhibited more activity in ventral regions. Oxytocin also led to inverse effects in reaction times on attribution task between groups, with controls getting faster and depressed individuals slower to respond. Conclusion: Depression is associated with increased paralimbic activity during emotional mental attribution of others, appearing to be distinctly modulated by oxytocin when compared to healthy controls. Further studies are needed to explore long-term exposure to pro-social neuropeptides on mood in depressed populations and assess their clinical relevance.